2001
DOI: 10.1017/s0021859601001320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stake sizes on some growth indices and yield of three cassava cultivars (Manihot esculenta)

Abstract: The effects of five stake weights (50, 63, 75, 88 and 100 g) of three cassava cultivars (TMS 30572, TMS 91934 and NR 8083) on the growth and yield of cassava were studied for 2 years (1992\93 and 1993\94) in Nigeria. The leaf area index (LAI), crop growth rate (CGR), net assimilation rate (NAR), leaf area duration (LAD), harvest yield and harvest index (HI) were dependent on the weight of stake planted and were greatest at the stake weight of 88 g (875 kg\ha) irrespective of cassava cultivar. Variations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The size and quality of stem are of fundamental importance for high yields (Eke-Okoro et al, 2001). Differences in weight of stem cuttings result in differences in food reserve (Okeke, 1998), and it is on this that the initial growth of the plant depends implying basically that stem weight or starch are associated to the establishment phase of cassava in the field.…”
Section: Key Early-growth Phase Phenotyping Methodology For Molecularmentioning
confidence: 99%
“…The size and quality of stem are of fundamental importance for high yields (Eke-Okoro et al, 2001). Differences in weight of stem cuttings result in differences in food reserve (Okeke, 1998), and it is on this that the initial growth of the plant depends implying basically that stem weight or starch are associated to the establishment phase of cassava in the field.…”
Section: Key Early-growth Phase Phenotyping Methodology For Molecularmentioning
confidence: 99%
“…where W 1 and W 2 are crop dry weight (mg) and L 1 and L 2 are leaf area (cm 2 ) at the times T 1 and T 2 (d), respectively (Eke-Okoro et al, 2001). The harvest index (HI) (Kawano, 1990) was computed using the following equation:…”
Section: Data Collectionmentioning
confidence: 99%
“…upland condition in Khon Kaen Province, Thailand, indicated that the crop traits (SRGR during 300-360 DAP,LGR during 60-120 DAP, and LGR during 300-360 DAP) were the components of physiological determinants of both total crop and storage root dry weights at final harvest Lahai et al (1999). Higher values of CGR and NAR of three different cassava genotypes(TMS 30572, TMS 91934, and NR 8083) were associated with the weight of planting material or stick that produced optimum storage root yield in Nigeria (5.4° N, 7.5° E; 122 m asl)(Eke-Okoro et al, 2001). Higher values of CGR and NAR of three different cassava genotypes(TMS 30572, TMS 91934, and NR 8083) were associated with the weight of planting material or stick that produced optimum storage root yield in Nigeria (5.4° N, 7.5° E; 122 m asl)(Eke-Okoro et al, 2001).…”
mentioning
confidence: 97%
“…Eke-Okoro (2000) assessed the photosynthetic efficiency and productivity of low and high cyanide cassava genotypes and reported that high cyanide cassava genotypes had better photosynthetic efficiency and higher storage root yield than low cyanide cassava genotypes. Also, cassava genotypes with profuse branching characters have the tendency to produce higher fresh root yield than the less branching types (Eke-Okoro et al, 2001).…”
Section: Introductionmentioning
confidence: 99%